The Transgressive Narratives of Hamsun's In Wonderland - Fjågesund, Peter (Nordlit, 2020)
The article focuses on the transgressive quality of Hamsun’s In Wonderland, that is on the book’s variety of literary genres and narrative techniques, and on the narrator’s equally transgressive presentation of himself. To examine these qualities more specifically, the paper discusses to what extent Hamsun’s travelogue is indebted to the novel that, according to Martin Nag, was essential for Hamsun’s journey to the Caucasus, namely Mikhail Lermontov’s A Hero of Our Time(1840). This will include an investigation of similarities of genre as well as similarities between Lermontov’s protagonist Pechorin and the narrator in In Wonderland, both of whom are discussed in relation to the Russian tradition of so-called “superfluous men”.